2021
DOI: 10.1111/medu.14542
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal qualitative research in medical education: Time to conceptualise time

Abstract: Longitudinal qualitative research (LQR) is an approach to research that entails generating qualitative data with the same participants for an extended time. The primary aim of LQR is to explore participants' lived experiences in real time as these experiences unfold, in other words, to explore their journey. 1,2 Although a body of LQR exists, it has yet to make substantial in-roads into medical education. 3 The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 46 publications
0
42
0
Order By: Relevance
“…Balmer et al have advocated greater use of longitudinal qualitative research in medical education, as recursive data allows exploration of the student’s own journey through time , and where time is fluid . [ 33 ] Respondents can reflect on the past and how their perceptions change in the light of recent experience. It is suggested that the trust and safe space generated in recursive data collection may encourage rather than discourage retention of participants in the research.…”
Section: Discussionmentioning
confidence: 99%
“…Balmer et al have advocated greater use of longitudinal qualitative research in medical education, as recursive data allows exploration of the student’s own journey through time , and where time is fluid . [ 33 ] Respondents can reflect on the past and how their perceptions change in the light of recent experience. It is suggested that the trust and safe space generated in recursive data collection may encourage rather than discourage retention of participants in the research.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast to discrete, crosssectional qualitative studies, longitudinal qualitative studies ask researchers to partner with participants and gain a rich understanding of their journeys as their journeys unfold. 22 This approach is also flexible enough to incorporate meaningful change not only in the participants but also the researchers. 21,22 In this four-year study, we initially conceptualised the graduate programme in medical education in which this study was situated as a community of practice.…”
Section: Methodological Underpinningsmentioning
confidence: 99%
“…22 This approach is also flexible enough to incorporate meaningful change not only in the participants but also the researchers. 21,22 In this four-year study, we initially conceptualised the graduate programme in medical education in which this study was situated as a community of practice. We realised, like Wenger, that we needed to broaden our perspective when the community of practice dissipated as participants graduated and moved on to others.…”
Section: Methodological Underpinningsmentioning
confidence: 99%
“…59 Moreover, longitudinal qualitative ego network research may overcome the limitations of rendering social relations as occurring in fixed, discrete moments of time. 60…”
Section: A Snapshot In Timementioning
confidence: 99%